Phenobarbital overdose in an eleven-year-old-girl with attempted suicide - V Lily Limantara; Made Widia; Ketut Suwitra; Endah Ardjana (Indonesian Pediatric Society Publishing House, 2016)
This report describes a patient with life-threat- ening phenobarbital overdose, treated successfully with hemodialysis, using a high-flux, high-efficiency dialyzer and high blood flow rates. The rapid fall in phenobarbital levels and the dramatic clinical re- sponse noted during the procedure supports this technique as an effective therapy in such patients.